Climate security mapping for targeted humanitarian and resilience WFP interventions in Mali: Climate security hotspots and food security insights - Sarzana, Carolina; Doehnert, Federico; Kenduiywo, Benson; Ndiaye, Abdoulaye; Sib, Ollo; Pacillo, Grazia; Läderach, Peter (2023)
Like other land-locked countries in Africa’s Sahel region, Mali is experiencing population pressures, more intense and variable drought cycles, and rising insecurity. Extreme temperatures and episodic rainfall are not unfamiliar to Mali but are going to become even more variable and intense as climates shift. These changes in climate are likely to severely impact the Malian economy and society which is extremely dependent on climate-sensitive sectors such as agriculture, livestock, fisheries and forestry. As the disruption caused by climate change has been rising, food insecurity has also been increasing. Other than climate, the society is also plagued by a weak governance marked by corruption and centralized rule, and experiences large ethnic divides. Various conflicts have ensued as a result of political and socio-economic factors, as well as climate exposure. The World Food Programme (WFP) in Mali plays a pivotal role in addressing these challenges through targeted interventions, encompassing climate-resilient agricultural practices, conflict-sensitive food distribution, and community-based resilience-building initiatives. WFP’s resileince programs are informed by an Integrated Context Analysis (ICA) which produces a series of maps that color-code areas of a country according to how they have historically experienced a particular condition or risk. Contrarily, WFP's humanitarian programs prioritize areas of intervention based on the results of the Cadre Harmonisé. The goal of this factsheet is to provide a climate security lens to these two analyses in order to define whether WFP intervention priorities are coherent to climate security hotspots. This analysis allows to inform WFP on whether it needs to review its target areas or add new ones.